Let's check:

We start with the following equality, which is true:

16-36 = 25-45

We add (81/4) on both sides, which does not change equality:

16-36+(81/4) = 25-45+(81/4)

This can be written as follows: (perfect square trinomial)

(4-(9/2))^{2} = (5-(9/2))^{2}

Apart from the square root on both sides we have:

4-(9/2) = 5-(9/2)

Adding (9/2) on both sides of equality we have:

4 = 5

As 4 = 2 + 2 we come to the following conclusion:

**2+2=5**

Obviously this demonstration has an error because we all know that 2 + 2 is not equal to 5 (or does anyone have any questions?). Click below to find out what the error is:

In this demonstration comes a stage where we have:

**(4-(9/2)) ^{2} = (5-(9/2))^{2}**

According to the demonstration, the next step is:

Take the square root on both sides, obtaining:

**4-(9/2) = 5-(9/2)**

**There is the mistake !!!**

It is wrong because **SQUARE ROOT** of a number **SQUARED** is equal to **MODULE** of this number. So the correct would be:

**| 4-(9/2) | = | 5-(9/2) |**

**| -0,5 | = | 0,5 |**

**0,5 = 0,5**